"The Value of Clinical Examination in Preterm Newborns after Neonatal Sepsis: A Cross-sectional Observational Study.". (17th February 2022) - Golin, Marina Ortega; Souza, Fabíola Isabel Suano; Paiva, Laércio da Silva; Sarni, Roseli Oselka Sacardo
ABSTRACT: Background: Neonatal sepsis is an important risk factor for lesions in the brain of preterm newborns (PTNB) and the most effective strategies to minimize its deleterious effects are early detection and intervention. Aim: To investigate the presence of neurological abnormalities in PTNBs after neonatal sepsis. Methods: This was a prospective cross-sectional study with 100 PTNBs selected at random, 50 of the study group (sepsis) and 50 of the control group (non-sepsis). The neurological evaluation protocol adopted was the Hammersmith Neonatal Neurological Examination (HNNE). Results: The PTNBs of the sepsis group had total HNNE scores lower than expected for normality in 86% of the cases, and the non-sepsis group in 26% ( p < .001). Higher prevalence levels of altered scores in tone category ( p < .001), tone patterns ( p = .026), reflexes ( p = .002), movements ( p < .001), abnormal signs ( p < .001) and behavior ( p < .001). Conclusion: The neurological dysfunctions after neonatal sepsis could be identified by clinical neonatal neurological evaluation.